Strategie przekładu a teorie postkolonialne na przykładzie tłumaczeń powieści Alaina Mabanckou - Wągrowska, Marta (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The translation of the postcolonial literature is a specific task. The translator needs to face challenges that arises from its particularity and finds himself involved in power relations, sociological and historical factors, questions of western cultural hegemony and national identity. It implicates also translator’s responsibility as his work will inevitably affect the perception of a dominated culture by former colonizers. As a consequence, the translation may become an instrument of decolonization, but it may also encourage Western stereotypes of colonized subjects and confirm the unequal status of cultures. In the postcolonial context, the translator needs to be also extremely accurate when it comes to intertextual references. Polish and English translations of Alain Mabanckou’s novel Broken Glass will serve us as an exemple to point out the challenges posed by postcolonial literature. We will analyze possible strategies of such translation and its consequences for the perception of the text.